2016
DOI: 10.1093/mnras/stw1810
|View full text |Cite
|
Sign up to set email alerts
|

The spectral slope and escape fraction of bright quasars atz∼ 3.8: the contribution to the cosmic UV background

Abstract: We use a sample of 1669 QSOs (r < 20.15, 3.6 < z < 4.0) from the BOSS survey to study the intrinsic shape of their continuum and the Lyman continuum photon escape fraction (f esc,q ), estimated as the ratio between the observed flux and the expected intrinsic flux (corrected for the intergalactic medium absorption) in the wavelength range 865-885Å restframe. Modelling the intrinsic QSO continuum shape with a power-law, F λ ∝ λ −γ , we find a median γ = 1.30 (with a dispersion of 0.38, no dependence on the reds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
82
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 42 publications
16
82
1
Order By: Relevance
“…This might seem at odds e.g. with the study of Grazian et al (2018), who found that for their sample of AGN, the average escape fraction is of the order of ∼ 75%, thus extending the earlier work of Cristiani et al (2016) on bright quasars. Similarly, Guaita et al (2016) detected LyC flux with a relative escape fraction f AGN esc rel ∼ 0.72 ± 0.18 for one object with M 1450 ∼ −21.9 at z ∼ 3.46, but they could only put upper limits on their other seven AGN.…”
Section: Contribution Of the Agn To The Lyc Leakagementioning
confidence: 58%
See 1 more Smart Citation
“…This might seem at odds e.g. with the study of Grazian et al (2018), who found that for their sample of AGN, the average escape fraction is of the order of ∼ 75%, thus extending the earlier work of Cristiani et al (2016) on bright quasars. Similarly, Guaita et al (2016) detected LyC flux with a relative escape fraction f AGN esc rel ∼ 0.72 ± 0.18 for one object with M 1450 ∼ −21.9 at z ∼ 3.46, but they could only put upper limits on their other seven AGN.…”
Section: Contribution Of the Agn To The Lyc Leakagementioning
confidence: 58%
“…The properties of faint AGN and their host are still unclear. For instance, while the observations of Cristiani et al (2016) suggest that the AGN escape fraction f AGN esc can reach high values for bright quasars, it is virtually unknown at the faint end. Grazian et al (2018) find a high relative f AGN esc for their sample at z ∼ 4, while the analysis of a sample of faint AGN selected in the SSA22 protocluster by Micheva et al (2017) is suggestive of f AGN esc being below unity at z ∼ 3 (although the sample size is small).…”
Section: Introductionmentioning
confidence: 99%
“…While it is traditionally assumed that f esc,QSO = 1 (for example, Haardt & Madau 2012), in principle it is possible that f esc,QSO varies with luminosity and redshift for QSOs just as in the case of galaxies. Indeed, recent observations indicate that f esc,QSO ≈ 0.7 in the case of bright QSOs at z ∼ 3 (Cristiani et al 2016). Furthermore, Micheva et al (2017) report observations of 14 faint QSOs at z ∼ 3 that are consistent with much lower values for f esc,QSO (including zero).…”
Section: The Quasar Uvbmentioning
confidence: 98%
“…Recent observations suggest that faint quasars may have made an unexpectedly large contribution to the high-redshift UVB (Giallongo et al 2015), although these observations are not irreconcilable with galaxydominated reionization (Jiang et al 2016;Ricci et al 2017). However, the former conclusion is only true if the fraction of ionizing photons that escape f esc from quasars is unity, and this conventional assumption may not be correct (Micheva et al 2017;Cristiani et al 2016). Further, other work has E-mail: cdoughty@nmsu.edu shown that reionization by faint active galactic nuclei would result in predictions of optical depth, neutral fractions, and ionizing emissivity that conflict considerably with observations (Hassan et al 2017).…”
Section: Introductionmentioning
confidence: 99%